2010
DOI: 10.1038/jid.2010.19
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Nonsense Mutation within the Dystonin Gene Coding for the Coiled-Coil Domain of the Epithelial Isoform of BPAG1 Underlies a New Subtype of Autosomal Recessive Epidermolysis Bullosa Simplex

Abstract: Epidermolysis bullosa (EB) is a group of autosomal dominant and recessive blistering skin diseases in which pathogenic mutations have been reported in 13 different genes encoding structural proteins involved in keratinocyte integrity, as well as cell-matrix or cell-cell adhesion. We now report an inherited skin fragility disorder with a homozygous nonsense mutation in the dystonin gene (DST) that encodes the coiled-coil domain of the epithelial isoform of bullous pemphigoid antigen 1, BPAG1-e (also known as BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
122
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 35 publications
(31 reference statements)
8
122
1
2
Order By: Relevance
“…Characteristics are a progressive loss of coordination of the limbs (ataxia) and an early death (Kothary et al 1988;Guo et al 1995). There are only few reports about patients with mutations of the human dystonin gene (Giorda et al 2004;Groves et al 2010;Edvardson et al 2012).Several dystonin isoforms are generated from one genomic locus of 400 kb. They are expressed in the central nervous system (CNS) (predominant neuronal isoform "a," 617 kDa and "n," 344 kDa), muscles (predominant muscle isoform "b," 834 kDa), and skin (predominant skin isoform "e," 302 kDa) ( Figure 1 Pool et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics are a progressive loss of coordination of the limbs (ataxia) and an early death (Kothary et al 1988;Guo et al 1995). There are only few reports about patients with mutations of the human dystonin gene (Giorda et al 2004;Groves et al 2010;Edvardson et al 2012).Several dystonin isoforms are generated from one genomic locus of 400 kb. They are expressed in the central nervous system (CNS) (predominant neuronal isoform "a," 617 kDa and "n," 344 kDa), muscles (predominant muscle isoform "b," 834 kDa), and skin (predominant skin isoform "e," 302 kDa) ( Figure 1 Pool et al 2005).…”
mentioning
confidence: 99%
“…They are expressed in the central nervous system (CNS) (predominant neuronal isoform "a," 617 kDa and "n," 344 kDa), muscles (predominant muscle isoform "b," 834 kDa), and skin (predominant skin isoform "e," 302 kDa) ( Figure 1 Pool et al 2005). In human patients, mutation of genes ranges from single base pair (bp) deletion and point mutation to translocation (Giorda et al 2004;Groves et al 2010;Edvardson et al 2012).In this study, a new mutation in the murine dystonin gene, Dst:g.274762_314056del (with respect to genomic DNA), for simplicity called "dt-MP," is described. For this, detailed morphological and molecular analyses of the CNS and peripheral organs were performed.…”
mentioning
confidence: 99%
“…The phenotype of mice with an epidermal-specific deletion of BPAG1 resembles that of bullous pemphigoid, a human skin disease in which patients produce autoantibodies against BPAG1 (Labib et al, 1986;Mueller et al, 1989;Diaz et al, 1990). Mutations in BPAG1 have also been found in humans with an inherited skin fragility disorder (Groves et al, 2010). Additionally, it has been showed that BPAG1e acts as an essential component of the signaling pathway by which β4-integrin regulates front-to-rear cell polarity and cell migration in skin (Michael et al, 2014).…”
Section: Cellular Functions Of Bpag1mentioning
confidence: 99%
“…As noted above, the epidermis of dt/dt mutant mice resembles that of bullous pemphigoid, a human disorder where autoantibodies against BPAG1 are produced (Diaz et al, 1990;Labib et al, 1986;Mueller et al, 1989). A BPAG1e-specific mutation has been found in humans with an inherited skin fragility disorder (Groves et al, 2010). This mutation within the coiled-coil domain of BPAG1e is associated with the loss of only the hemidesmosomal inner plaque.…”
Section: Bpag1 In Epidermolysis Bullosa Simplexmentioning
confidence: 99%
See 1 more Smart Citation